KEDUDUKAN HAK WARIS ANAK ANGKAT DALAM HUKUM POSITIF INDONESIA - NI LUH ARININGSIH SARI (Universitas Mahasaraswati K. Mataram, 2023)
In a marriage, husband and wife are not always blessed with a child. To realize the dream of this married couple, many adopt children or adopt children as adopted children. the process of implementing child adoption which is carried out according to custom (customary law) and based on a court decision is valid and legally attached to the child's rights and obligations as a child to his adoptive parents. What is the status of the adopted child's inheritance rights in Indonesian Positive Law? That the position of the inheritance rights of adopted children in Indonesian positive law, namely based on the Civil Code/BW, Islamic law and customary law have differences in the implementation of social life. According to the inheritance law in the Civil Code which refers to Burgerlijk Wetboek (BW) does not directly mention the term adopted child/adopted child, that's why Staatsblad Number 129 of 1917 was made as a complement to BW in regulating this problem. As a result of the law of adoption regulated in the Staatblaad. 1927 No. 129, namely Article 11 explains that the adopted child legally obtains the name of the adoptive father, and Article 12 paragraph (1) states that adopted children are made as children born from the marriage of adoptive parents. So it can be said that the adopted child becomes the heir of the adoptive parents because the adoption causes the termination of all civil relations between the child and his biological parents. In Islam, foster or adopted children are not entitled to inheritance. however, Islamic law does not completely rule out the opportunity for adopted children to get a share of the assets of their adoptive parents, that is, adopted children are entitled to an obligatory will which amounts to no more than 1/3 of a part, this is as stated in Article 209 KHI (Compilation of Islamic Law ). Meanwhile, according to customary law, the position of inheritance rights for adopted children refers to the customary law system of each region because customary law recognizes the kinship system, namely the patrilineal, matrilineal and parental kinship systems which will later affect the inheritance position of adopted children in the kinship system.